2022
DOI: 10.1039/d1tb02241e
|View full text |Cite
|
Sign up to set email alerts
|

Mussel-inspired injectable chitosan hydrogel modified with catechol for cell adhesion and cartilage defect repair

Abstract: Repairing articular cartilage defect is a great challenge due to the poor self-regenerative capability of cartilage. Hydrogel-based tissue engineering has been considered as an effective strategy. In this study, inspired...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 41 publications
(36 reference statements)
0
23
0
Order By: Relevance
“…Considering the risk of byproduct toxicity, emerging cross-linking strategies involve enzymatic reactions [ 181 ]. Siqi Zhou et al [ 182 ] reported on the functionalization of CHT with 3,4-dihydroxyhydrocinnamic acid, followed by oxidative cross-linking through horseradish peroxidase/hydrogen peroxide (HRP/H 2 O 2 ) ( Scheme 10 ).…”
Section: Chitosan-based Hydrogels For Biomedical Applicationsmentioning
confidence: 99%
“…Considering the risk of byproduct toxicity, emerging cross-linking strategies involve enzymatic reactions [ 181 ]. Siqi Zhou et al [ 182 ] reported on the functionalization of CHT with 3,4-dihydroxyhydrocinnamic acid, followed by oxidative cross-linking through horseradish peroxidase/hydrogen peroxide (HRP/H 2 O 2 ) ( Scheme 10 ).…”
Section: Chitosan-based Hydrogels For Biomedical Applicationsmentioning
confidence: 99%
“…[31a,164] These materials include films, [165] particles, [142] fibers, [139,166] foams, [167] and hydrogels. [141,168] It has been extensively used in the biomedical field because of its biodegradability and biocompatibility.…”
Section: Chitin and Chitosanmentioning
confidence: 99%
“…With the increase of amplification generations, chondrocytes lose their chondrogenic phenotype. Eventually, this results in lower cartilage repair ( Cai et al, 2020 ; Zhou et al, 2022 ). Autologous chondrocytes are mainly derived from natural cartilage in the non-weight-bearing region of the joint, which may lead to donor site disease ( Chen et al, 2018 ).…”
Section: Materials Of Injectable Hydrogelsmentioning
confidence: 99%